Vector routing protocols for Delay Tolerant Networks. (6th July 2010) - Kang, Hyunwoo; Kim, Dongkyun
In Delay Tolerant Networks (DTNs) with frequent network partitioning, routing packets is a challenge, because the successful establishment of an end-to-end path between source and destination nodes is not guaranteed. Typical routing protocols for DTNs depend on data replications over multiple paths for reliable data delivery. Since they invoke a lot of replicated packets, we propose three efficient Vector Routing protocols based on the vector of node movements in order to reduce the number of such replications: Flooding-based, History-based and Location-aware Vector Routing protocols. Using ns-2 simulation with two different mobility models, we verify that Vector Routing protocols show better performance than other existing protocols in terms of less amount of traffic incurred without loss of packet delivery ratio.